دلالات (ما) في القرآن الكريم وترجماتها إلى اللغة الإنجليزية - Nur Afifah binte Kamarazaman (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study is entitled: "The Meanings of (Ma) in the Holy Quran and its Translations to English Language". The word (ma) is mentioned in the Holy Quran in more than 2500 places, hence, the importance of this study. This huge number signifies the importance of exploring the meaning of (ma) and observing it to understand the Book of Allah although this is not easy, as scholars and interpreters differ in explaining and interpreting the word (ma) due to its various meanings. The differences in interpreting the meanings of (ma) have led the translators to differ in the transfer of meanings of (ma) in the Holy Quran to the target language. In glorifying the book of Allah, this study attempts by means of descriptive, inductive and analytical methods, to identify the most important meanings of (ma) which are al-Mausulah, al-Syartiyyah, al-Istifhamiyyah, al-Ta'ajjubiyyah, al-Nafiyah, al-Zaidah and al-Masdariyyah, through the analysis of five approved translations for the meanings of the Quran in the English language, and explaining the translators' efforts in dealing with the meanings of (ma) in the Holy Quran and the lexical transfer of the meanings to the English language in order to ascertain the closest and most accurate translation to the linguistic meaning of (ma). This research concludes that in translating the meanings of (ma), the translators relied on a number of methods: literal translation, interpretation, deletion, addition and substitution. Finally, this paper recommends the necessity of ensuring that the transfer of meaning of all words in the text of the Quran to the target language is done with utmost honesty and accuracy to avoid falling into confusion, error and distortion.